AI and Louis Kahn's Exeter Library: Reimagining Monumentality, Materiality, and Human Experience through Generative Design - Hidayet Softaoğlu (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA, 2025)
This research paper explores a central and timely question: Can artificial intelligence understand architectural meaning? Using Louis Kahn's theory of "served" and "servant" spaces as a philosophical framework, the study investigates how AI interprets architecture beyond formal simulation into the realms of ethics, atmosphere, and symbolic structure. As one of Kahn's most iconic works, the Exeter Library exemplifies monumental form, human-centred space, and material spirituality. By generating visual outputs using MidJourney and evaluating them through five analytical categories—monumentality, spatial order, light, material, and semiotics—this research examines whether AI can approximate meaningful architecture's emotional and metaphysical essence. While AI tools offer impressive capabilities regarding efficiency, environmental responsiveness, and form generation, they often struggle to grasp the humanistic, symbolic, and moral dimensions embedded in architecture. This paper argues that when guided by architectural theory and evaluated through semiotic frameworks, AI can act as a generator of form and as a reader of architectural values.